Relationship between running intensity, muscle activation, and stride kinematics during an incremental protocol - Castro, A.; LaRoche, D. P.; Fraga, C. H. W.; Gonçalves, M. (Science & Sports, 2013)
Objective: To analyze the effect of running intensity on stride length (SL), stride frequency (SF), stride time (ST) and the electromyographic signal of the rectus femoris (RF), vastus lateralis (VL), vastus medialis (VM), tibialis anterior (TA), biceps femoris (BF) and gastrocnemius lateralis (GL) muscles. Methods: Nine well-trained runners performed an incremental protocol with an initial velocity of 10 km.h-1, and increments of 1 km.h-1 every 3 minutes until exhaustion. The electromyographic activity, SL, SF, ST, inter-stride coefficient of variation, and association between kinematic and electromyographic parameters were calculated at 60%, 80% and 100% of maximum running velocity. Results: SL, SF and electromyographic activity of the RF, VM, VL and GL increased and the ST decreased with increased running speed. Electromyographic variability of VL and VM was higher than GL, and variability was lower in TA than all other muscles. The inter-stride variability of muscle activation was associated with kinematic parameters, and their variability, differently as running speed increased. Conclusion: The incremental protocol increased electromyographic activity differently among lower limb muscles; increased SF and SL, and decreased ST, without changing the variability of these variables. Muscle activation variability was correlated with kinematic parameters, but the relationships among these measures varied with running intensity.